PENGUJIAN BEBERAPA KONSENTRASI GIBERELIN PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY YANG MENGALAMI CEKAMAN GENANGAN AIR - Esyka ' '; Gunawan ' Tabrani; Fetmi ' Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Seedling is a plant material which is very important in the development of the palm oil industry. Quality of seedlings will determine the success of oil palm cultivation. The uncertain climate change caused many oil palm nursery are flooding. This stage of hypoxia or anoxia caused plant growth stress. Therefore has been tested multiple giberelin concentrations and flooding against oil palm seedlings on pre nurseries. This research aims to maintaining quality of oil palm seedlings of waterlogging stress by providing some gibberellin concentration. This research was conducted at the experiment station of Agriculture Faculty University of Riau, Pekanbaru from June to September 2015. The experiment using the completely randomized factorial design 3 x 3 and 3 replications. The first factor are g0 = without gibberellin, g1 = 150 ppm gibberellin and g2 = 300 ppm gibberellin, and the second factor is duration of waterlogging stress. There are w0 = 0 days, w1 = 25 days and w2 = 50 days. The results is no interaction of gibberellin concentration and flooding stress to oil palm seedling. The higher concentration of gibberellin given caused higher seedlings, and the growth of diameter rod and adventitious roots was affected by flooding. Keywords: pre nursery, gibberellin, waterlogging stress